Oliver Tambo and the struggle against apartheid - Tambo, Oliver, 1917-; Reddy, E. S. (Sterling Publishers, in collaboration with Namedia Foundation, 1987)
Festschrift honoring Oliver Tambo, b. 1919, South African freedom fighter; comprises transcript of his speeches and articles by authors on apartheid.